2003
DOI: 10.1152/jn.01041.2001
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatases Mediate Depotentiation Induced by High-Intensity Theta-Burst Stimulation

Abstract: Wilson. Protein phosphatases mediate depotentiation induced by highintensity theta-burst stimulation. J Neurophysiol 89: 684 -690, 2003; 10.1152/jn.01041.2001. We have previously reported that varying stimulus intensity produces qualitatively different types of synaptic plasticity in area CA1 of hippocampal slices: brief low-intensity (LI) theta-burst (TB) stimuli induce long-term potentiation (LTP), but if the stimulus intensity is increased (to mimic conditions that may exist during seizures), LTP is not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
(30 reference statements)
6
24
0
Order By: Relevance
“…Other forms of metaplasticity involve other routes of Ca 2ϩ entry, for instance, via NMDA receptors (Philpot et al, 2007). Our data that metaplastic modifications downstream of L-type Ca 2ϩ channels in TNRϪ/Ϫ mice involve the protein phosphatases PP1 and PP2A are in agreement with studies showing that activation of PP1/PP2A leads to reversal of LTP (Huang et al, 2001;Kang-Park et al, 2003) and prevents induction of late phases of LTP (Woo and Nguyen, 2002), whereas inhibition of PP1 reduces the threshold for induction of LTP (Jouvenceau et al, 2006). Signaling downstream of PP1/ PP2A may involve dephosphorylation of transcription factors, such as the cAMP response element-binding protein (Hagiwara et al, 1992;Wadzinski et al, 1993), the AMPA glutamate receptor subunit 1 (Huang et al, 2001), stargazin, which is important for synaptic expression of AMPA receptors (Tomita et al, 2005), and several protein kinases, including extracellular signal-regulated kinases (Norman et al, 2000), protein kinase C , and Ca 2ϩ /calmodulin-dependent protein kinase II (Strack et al, 1997;Huang et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other forms of metaplasticity involve other routes of Ca 2ϩ entry, for instance, via NMDA receptors (Philpot et al, 2007). Our data that metaplastic modifications downstream of L-type Ca 2ϩ channels in TNRϪ/Ϫ mice involve the protein phosphatases PP1 and PP2A are in agreement with studies showing that activation of PP1/PP2A leads to reversal of LTP (Huang et al, 2001;Kang-Park et al, 2003) and prevents induction of late phases of LTP (Woo and Nguyen, 2002), whereas inhibition of PP1 reduces the threshold for induction of LTP (Jouvenceau et al, 2006). Signaling downstream of PP1/ PP2A may involve dephosphorylation of transcription factors, such as the cAMP response element-binding protein (Hagiwara et al, 1992;Wadzinski et al, 1993), the AMPA glutamate receptor subunit 1 (Huang et al, 2001), stargazin, which is important for synaptic expression of AMPA receptors (Tomita et al, 2005), and several protein kinases, including extracellular signal-regulated kinases (Norman et al, 2000), protein kinase C , and Ca 2ϩ /calmodulin-dependent protein kinase II (Strack et al, 1997;Huang et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…5 A, C), supporting the view that these channels constitute an important route for Ca 2ϩ entry necessary for induction of metaplasticity. Because sustained Ca 2ϩ entry may stimulate the activity of protein phosphatases, we treated slices with the inhibitor of PP1/2A, calyculin A, known to prevent some forms of metaplasticity (Huang et al, 2001;Woo and Nguyen, 2002;Kang-Park et al, 2003). This treatment dramatically increased LTP in TNRϪ/Ϫ mice to 196.5 Ϯ 19.9%, compared with 157.1 Ϯ 14.0% recorded in TNRϩ/ϩ mice (Fig.…”
Section: Analysis Of Molecular Mechanisms Involved In Induction Of Mementioning
confidence: 97%
“…7D) (140 Ϯ 15%; N ϭ 54 spines/6 cells; p ϭ 0.95 compared with control spine expansion). It has been suggested that PP1 can be endogenously inactivated by PKA (Kang-Park et al, 2003;Makhinson et al, 2006), and so we would anticipate that persistently elevated PKA activity in the postsynaptic cell would have an effect similar to that of okadaic acid. We tested this possibility by including 8-Br-cAMP in the recording pipette solution, and we repeated the above experiments using LFS.…”
Section: Spine Stabilization and Ltp Consolidation Are Both Disruptedmentioning
confidence: 99%
“…Within this time window, LTP can be depotentiated by low-frequency activity (LFS), through a mechanism that requires PP1 (O'Dell et al, 1994;Zhou et al, 2003). PKA can prevent depotentiation by leading to phosphorylation of inhibitor 1, which in turn inhibits PP1 (Kang-Park et al, 2003;Makhinson et al, 2006). To determine whether the consolidation of spine expansion is subject to reversal through mechanisms that are similar to those involved in depotentiation, we examined whether spine expansion is subject to activity-dependent reversal, and if so, whether the same mechanisms are involved in this reversal of spine expansion as in synaptic depotentiation.…”
Section: Spine Stabilization and Ltp Consolidation Are Both Disruptedmentioning
confidence: 99%
“…In contrast, high pathological concentrations of glutamate stimulated dephosphorylation of Ser 847 -PO 4 . The first of these effects may share similarity with a form of long term potentiation induced by theta pulse stimulation of hippocampal neurons which promotes the activation of CaMKII (31,32), whereas the second may relate to excitotoxicity after stroke and spinal cord injury which has been shown to involve induction of phosphatases (33)(34)(35)(36). Strikingly, after the 5 M glutamate induction of phosphorylation of nNOS at Ser 847 , nNOS remains sensitive to subsequent dephosphorylation when neurons are exposed to the excitotoxic glutamate concentration.…”
Section: Nnosmentioning
confidence: 99%